Histopathological changes in the reproductive organs of does with pregnancy toxaemia and their aborted foetuses - Zainal Ulum, Muhamad Taqiyudin; Ab Azid, Muhamad Affan; Shen, Tong Wei; Hassim, Hasliza Abu; Zamri-Saad, Mohd; Salleh, Annas (Elsevier BV, 2021)
Pregnancy toxaemia (PT) is a metabolic disorder affecting does during late gestation. This study describes the histopathological changes in pregnant does and their foetuses experimentally-induced with PT. Eight does in their late pregnancy were induced into PT by reducing the energy intake (Group 1), while 6 does were maintained with adequate energy intake (Group 2). The blood beta-hydroxybutyric acid (BHBA) and glucose concentrations were measured every 5 days throughout the 20-day study period. All does that experienced stillbirth were immediately euthanised, while the does and the full-term, non-aborted foetuses were euthanised on day 20. Samples of umbilical cords, placentas and uteri were collected from the does, while hearts and livers were collected from the foetuses. The samples were subjected to histopathological assessment, and subsequently correlated with the blood BHBA concentration. Stillbirth occurred in 5 (62.5 %) does of Group 1. The remaining does of Group 1 and all does of Group 2 did not experience stillbirth until the end of the experiment. Overall lesions in the umbilical cord were significantly (p < 0.01) more severe in Group 1. Does of Group 1 that experienced stillbirth showed chorionic villi necrosis and homogenous chorionic villi hypomaturity, while the endometrial glands were non-secreting. The stillborn foetuses showed extensive hepatic necrosis. The last concentrations of BHBA and glucose showed significant (p < 0.05) difference between the two groups. The histopathological lesions in the placenta, uterus, and foetal liver were significantly (p < 0.05−0.01) correlated with the blood BHBA concentration. The histopathology lesions could suggest the mechanism of stillbirth in PT and raise concern that it could affect the performance of the off-springs should stillbirth did not occur.